2003
DOI: 10.1161/01.str.0000098901.97350.7d
|View full text |Cite
|
Sign up to set email alerts
|

How Effective Are “Community” Stroke Screening Programs at Improving Stroke Knowledge and Prevention Practices?

Abstract: Background and Purpose-Community stroke screening is a commonly used prevention strategy to identify and educate those at risk. Although the goal of this approach is to reduce the overall occurrence of stroke, its long-term benefit remains unknown. The purpose of this study was to determine whether attendance of a stroke screening changes knowledge or prevention practices in persons at risk for stroke 3 months later. Methods-A stroke screening event was held following the National Stroke Association guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 6 publications
0
38
1
3
Order By: Relevance
“…Only 27% of patients attending the screening had implemented an intervention to decrease stroke risk. 305 Similar studies showed that Ϸ50% of those attending a stroke screening made at least 1 behavioral change to reduce stroke risk and that community education improved the participant's knowledge of stroke warning signs and symptoms. 306 -308 The National Stroke Association states that "80% of strokes can be prevented" (http://www.stroke.org/site/ PageServer?pagenameϭPREVENT).…”
Section: The Nurse's Role In Stroke Education In the Communitymentioning
confidence: 94%
See 1 more Smart Citation
“…Only 27% of patients attending the screening had implemented an intervention to decrease stroke risk. 305 Similar studies showed that Ϸ50% of those attending a stroke screening made at least 1 behavioral change to reduce stroke risk and that community education improved the participant's knowledge of stroke warning signs and symptoms. 306 -308 The National Stroke Association states that "80% of strokes can be prevented" (http://www.stroke.org/site/ PageServer?pagenameϭPREVENT).…”
Section: The Nurse's Role In Stroke Education In the Communitymentioning
confidence: 94%
“…303, 304 The effect of stroke screening on knowledge and behavioral changes has been studied. 305 One screening used the National Stroke Association guidelines. Participants were evaluated before and after screening and 3 months after the event.…”
Section: The Nurse's Role In Stroke Education In the Communitymentioning
confidence: 99%
“…A recent study showed that the effect of the health education programme on knowledge and warning signs of stroke decreased at 3 months of follow-up (14) . However, the present study showed that a family-based nutrition health education programme on blood pressure lowering had significant effectiveness at 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…8,20 Based on the theory that awareness of stroke warning signs is needed to ensure individuals recognize and seek immediate medical attention, [21][22][23] over the past 2 decades considerable time, money, and efforts have been expended on assessing the level of public knowledge 21,24 -37 and the effect of awarenessbuilding initiatives, including mass media campaigns. 21,27,39,40 However, research on the relationship between knowledge of stroke warning signs and time to presentation at hospital remains limited, and the ability of advertising to shorten time to presentation is unclear. In 1992, Alberts et al 41 reported that an educational campaign increased the proportion of patients arriving at a specialist (tertiary) medical facility within 24 hours from 39.2% to 85.5%, and a 2000 study of 259 stroke patients in the Philippines found that failure to recognize symptoms as serious and stroke-related was associated with delayed presentation.…”
mentioning
confidence: 99%